Tree House Concept pada Rancangan Sekolah Alam di Keliki, Gianyar - Saputra, Yoby; ., Widiastuti; Swanendri, Ni Made (Jurnal Arsitektur Universitas Udayana; Vol 10 No 01 (2022): Jurnal Arsitektur, Universitas UdayanaDO - 10.24843/jaunud.v10i01.74845, 2022)
The role of architecture in education field is to design a convenience space for teaching and learning. The aim of tree house concept is to increase students’ learning enthusiasm in Indonesia. Tree house is a platform or building  built among the trees or in between the trees. Tree house based nature school is located at Keliki Gianyar, because of its nature and Gianyar government vision are align with this concept. Tree house concept doesn’t only refer to a house but can be applied on any architecture typology. The Core principle of this concept are saving the trees, further focus on flexibility for teaching and learning, achieve harmony with nature, and the structure able to resist the lateral load of moving trees in a tree house platform. The purpose of this research is designing nature school with Tree house concept. This research use descriptive analysis method and the result of this research is nature school with Tree house concept that can increase students’ learning enthusiasm .